A double perovskite / silica nanocomposite material, a preparation method and application thereof
Patent Information
- Application Number
- CN202410181873.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-02-18
- Publication Date
- 2026-10-27
- Estimated Expiration
- 2044-02-18
AI Technical Summary
然而,这类钙钛矿材料的本征稳定性较差,光学性能易受水、氧气及光照等因素的影响
[0022]本发明提供了上述技术方案所述的制备方法制备得到双钙钛矿/二氧化硅纳米复合材料。本发明提供的复合材料中:功能化二氧化硅附着在Cs2ZrCl6表面。本发明提供的复合材料在保持Cs2ZrCl6高荧光量子效率的同时,还显著提高了Cs2ZrCl6的储存稳定性。
Smart Images

Figure CN118027955B_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the technical field of lead-free halide perovskite materials, specifically relating to a double perovskite / silica nanocomposite material, its preparation method, and its application. Background Technology
[0002] Currently, lead-free halide perovskite materials exhibit high fluorescence quantum efficiency, showing promising application prospects in lighting, displays, and other fields. However, these perovskite materials suffer from poor intrinsic stability, and their optical properties are easily affected by factors such as water, oxygen, and light exposure. Therefore, the preparation of lead-free perovskites with high stability and high fluorescence quantum efficiency is of great significance. Summary of the Invention
[0003] The purpose of this invention is to provide a double perovskite / silica nanocomposite material, its preparation method and application. The double perovskite / silica nanocomposite material provided by this invention maintains the high fluorescence quantum efficiency of Cs2ZrCl6 while significantly improving the storage stability of Cs2ZrCl6.
[0004] To achieve the above objectives, the present invention provides the following technical solution:
[0005] This invention provides a method for preparing a double perovskite / silica nanocomposite material, comprising the following steps:
[0006] Cesium salt and hydrochloric acid are mixed to obtain a cesium salt solution;
[0007] Zirconium salt, hydrochloric acid, and functionalized silica are mixed to obtain a zirconium salt mixed solution, wherein the functionalized silica includes one or more of SiO2-NH2, SiO2-SH, and SiO2-SCN;
[0008] The cesium salt solution is injected into the zirconium salt mixed solution to obtain the double perovskite / silica nanocomposite material.
[0009] Preferably, the method for preparing the functionalized silica includes the following steps:
[0010] Hydrogen peroxide, concentrated sulfuric acid, and silicon dioxide were mixed and subjected to a hydroxylation reaction to obtain SiO2-OH;
[0011] The SiO2-OH, alcohol solvent, and functionalizing reagent are mixed and modified to obtain the functionalized silica. The functionalizing reagent includes one or more of the following: amino-containing silane coupling agents, mercapto-containing silane coupling agents, and thiocyanate-containing silane coupling agents.
[0012] Preferably, the functionalizing agent includes one or more of 3-aminopropyltriethoxysilane, 3-mercaptopropyltriethoxysilane, and 3-thiocyanopropyltriethoxysilane.
[0013] Preferably, the molar ratio of the cesium salt to the zirconium salt is (0.5–80):(0.25–40).
[0014] Preferably, the ratio of the zirconium salt to the functionalized silica is (0.25–40) mmol: (0.01–1.6) g.
[0015] Preferably, the concentrated sulfuric acid has a mass percentage content of ≥98%, the volume ratio of hydrogen peroxide to concentrated sulfuric acid is 1:1, and the amount ratio of hydrogen peroxide to silicon dioxide is (10-50) mL: (0.1-0.5) g.
[0016] Preferably, the alcohol solvent is ethanol; the ratio of SiO2-OH, alcohol solvent and functionalizing reagent is (0.1-0.4) g : (5-20) mL : (0.5-2) mL.
[0017] Preferably, the method for preparing the silicon dioxide includes the following steps:
[0018] The silicon dioxide is obtained by hydrolyzing a mixture of ethanol, water, ammonia, and tetraethyl orthosilicate to obtain the silicon dioxide. The mass percentage of the ammonia is 25-28%, and the volume ratio of the ethanol, water, ammonia, and tetraethyl orthosilicate is (250-500):(20-40):(8-16):(15-30). The hydrolysis reaction is carried out at a temperature of 35-50°C for 2.5-4 hours.
[0019] The present invention provides a preparation method described in the above technical solution to prepare a double perovskite / silica nanocomposite material.
[0020] This invention provides the application of the double perovskite / silica nanocomposite material described above in the preparation of lighting materials or display materials.
[0021] This invention provides a method for preparing a double perovskite / silica nanocomposite material, comprising the following steps: mixing cesium salt and hydrochloric acid to obtain a cesium salt solution; mixing zirconium salt, hydrochloric acid, and functionalized silica to obtain a zirconium salt mixed solution, wherein the functionalized silica includes one or more of SiO2-NH2, SiO2-SH, and SiO2-SCN; and injecting the cesium salt solution into the zirconium salt mixed solution to obtain the double perovskite / silica nanocomposite material. This invention uses functionalized silica as a spacer layer for Cs2ZrCl6, resulting in a composite material in which silica adheres to the perovskite surface, successfully synthesizing double perovskite / silica nanocomposite materials (Cs2ZrCl6@SiO2-NH2, Cs2ZrCl6@SiO2-SH, and Cs2ZrCl6@SiO2-SCN in the examples). While maintaining the high fluorescence quantum efficiency of Cs2ZrCl6, the storage stability of Cs2ZrCl6 is also significantly improved. Meanwhile, the preparation method provided by this invention is simple, and significantly improves the stability of double perovskite without changing the original preparation process and equipment of Cs2ZrCl6 double perovskite, making it suitable for industrial production.
[0022] This invention provides a method for preparing a double perovskite / silica nanocomposite material as described in the above-mentioned technical solution. In the composite material provided by this invention, functionalized silica is attached to the surface of Cs₂ZrCl₆. The composite material provided by this invention maintains the high fluorescence quantum efficiency of Cs₂ZrCl₆ while significantly improving the storage stability of Cs₂ZrCl₆. Attached Figure Description
[0023] Figure 1 XRD patterns of the products prepared in Examples 1-3 and Comparative Example 1;
[0024] Figure 2 SEM images of the products prepared in Examples 1-3 and Comparative Example 1;
[0025] Figure 3 The absolute quantum efficiency (PLQY) of the products prepared in Examples 1-3 and Comparative Example 1;
[0026] Figure 4 Storage stability (112 days) of the products prepared in Examples 1-3 and Comparative Example 1. Detailed Implementation
[0027] This invention provides a method for preparing a double perovskite / silica nanocomposite material, comprising the following steps:
[0028] Cesium salt and hydrochloric acid are mixed to obtain a cesium salt solution;
[0029] Zirconium salt, hydrochloric acid, and functionalized silica are mixed to obtain a zirconium salt mixed solution, wherein the functionalized silica includes one or more of SiO2-NH2, SiO2-SH, and SiO2-SCN;
[0030] The cesium salt solution is injected into the zirconium salt mixed solution to obtain the double perovskite / silica nanocomposite material.
[0031] In this invention, unless otherwise specified, all raw materials / components used in the preparation are commercially available products well known to those skilled in the art.
[0032] This invention involves mixing a cesium salt and hydrochloric acid (hereinafter referred to as the first hydrochloric acid) to obtain a cesium salt solution. In this invention, the cesium salt is preferably CsCl. The mass percentage of the first hydrochloric acid is preferably 36-38%. The preferred ratio of the cesium salt to the first hydrochloric acid is (0.5-80) mmol : (0.625-100) mL, more preferably (1-40) mmol : (1-50) mL, even more preferably (1.5-20) mmol : (2-20) mL, and specifically preferably 2 mmol : 2.25 mL.
[0033] This invention involves mixing zirconium salt, hydrochloric acid (hereinafter referred to as second hydrochloric acid), and functionalized silica to obtain a zirconium salt mixed solution. The functionalized silica includes one or more of SiO2-NH2, SiO2-SH, and SiO2-SCN. In this invention, the zirconium salt is preferably zirconium chloride. The mass percentage of the second hydrochloric acid is preferably 36-38%. The preferred ratio of the zirconium salt to the second hydrochloric acid is (0.25-40) mmol:(1.35-216) mL, more preferably (0.5-30) mmol:(1.5-200) mL, further preferably (0.75-10) mmol:(2-50) mL, and specifically preferably 1 mmol:2.7 mL. The molar ratio of the cesium salt to the zirconium salt is (0.5-80):(0.25-40), more preferably 2:1.
[0034] In this invention, the method for preparing the functionalized silica preferably includes the following steps:
[0035] Hydrogen peroxide, concentrated sulfuric acid, and silicon dioxide were mixed and subjected to a hydroxylation reaction to obtain SiO2-OH;
[0036] The SiO2-OH, alcohol solvent, and functionalizing reagent are mixed and modified to obtain the functionalized silica. The functionalizing reagent includes one or more of the following: amino-containing silane coupling agents, mercapto-containing silane coupling agents, and thiocyanate-containing silane coupling agents.
[0037] This invention involves a hydroxylation reaction of hydrogen peroxide, concentrated sulfuric acid, and silicon dioxide to obtain SiO2-OH. The preferred method for preparing the silicon dioxide includes the following steps: a hydrolysis reaction of ethanol, water, ammonia, and tetraethyl orthosilicate to obtain the silicon dioxide. The preferred mass percentage of ammonia is 25-28%. The preferred volume ratio of ethanol, water, ammonia, and tetraethyl orthosilicate is (250-500):(20-40):(8-16):(15-30), more preferably 250:20:8:15. The mixing of ethanol, water, ammonia, and tetraethyl orthosilicate includes the following steps: premixing the ethanol, water, and ammonia to obtain a premixed solution; and mixing the premixed solution with the tetraethyl orthosilicate. The preferred temperature for premixing is room temperature, and the preferred time is 1 hour. Premixing is preferably carried out under stirring conditions. The hydrolysis reaction is preferably carried out under water bath conditions. The preferred temperature for the hydrolysis reaction is 35–50°C, more preferably 40°C. The preferred time for the hydrolysis reaction is 2.5–4 hours, more preferably 3 hours. After the hydrolysis reaction is completed, a hydrolysis reaction solution is obtained. Preferably, the hydrolysis reaction solution is subjected to solid-liquid separation, and the obtained solid product is washed and dried sequentially to obtain the silica. The solid-liquid separation is preferably centrifugation. The washing reagents are preferably deionized water and ethanol, and the washing is preferably performed a total of 4 times, including 2 times with deionized water and 2 times with ethanol. The drying is preferably vacuum drying, and the preferred temperature for vacuum drying is 60°C. The drying is preferably carried out in a vacuum oven. This invention uses a gelation method to prepare silica, which can obtain silica microspheres with high sphericity. The silica preparation method provided by this invention is simple and easy to implement.
[0038] In this invention, the mass percentage of concentrated sulfuric acid is preferably ≥98%. The volume ratio of hydrogen peroxide to concentrated sulfuric acid is preferably 1:1. The ratio of hydrogen peroxide to silicon dioxide is preferably (10-50) mL:(0.1-0.5) g, more preferably 20 mL:0.2 g. In this invention, the mixing of hydrogen peroxide, concentrated sulfuric acid, and silicon dioxide preferably includes the following steps: mixing hydrogen peroxide and concentrated sulfuric acid to obtain a mixed solution; mixing the mixed solution with silicon dioxide. The temperature of the hydroxylation reaction is preferably room temperature, and the time is preferably 10 min. The hydroxylation reaction is preferably carried out under stirring. After the hydroxylation reaction is completed, a hydroxylation reaction solution is obtained. In this invention, the hydroxylation reaction solution is preferably separated into solid and liquid components, and the obtained solid product is washed with water and dried to obtain SiO2-OH. The solid-liquid separation is preferably centrifugation. The water washing is preferably ultrapure water washing, and the number of water washings is preferably 3 times. The drying is preferably vacuum drying, and the temperature of the vacuum drying is preferably 80°C, and the time is preferably 1 h. The drying is preferably carried out in a vacuum oven.
[0039] After obtaining SiO2-OH, the present invention modifies the SiO2-OH, alcohol solvent, and functionalizing reagent by mixing them to obtain the functionalized silica. The functionalizing reagent includes one or more of amino-containing silane coupling agents, mercapto-containing silane coupling agents, and thiocyano-containing silane coupling agents. In the present invention, the alcohol solvent is preferably ethanol. The functionalizing reagent preferably includes one or more of 3-aminopropyltriethoxysilane, 3-mercaptopropyltriethoxysilane, and 3-thiocyanopropyltriethoxysilane. The preferred ratio of SiO2-OH, alcohol solvent, and functionalizing reagent is (0.1-0.4) g:(5-20) mL:(0.5-2) mL, more preferably 0.3 g:10 mL:1 mL. The modification temperature is preferably room temperature, and the modification time is preferably 20 h. The modification is preferably carried out under stirring conditions. After the modification is completed, a modified reaction solution is obtained. The present invention preferably separates the modified reaction solution into solid and liquid phases, washes and dries the obtained solid product to obtain the functionalized silica. The solid-liquid separation is preferably centrifugation. The washing reagent is preferably ethanol, and the washing is preferably performed three times. The drying is preferably vacuum drying, with a preferred temperature of 80°C and a preferred time of 1 hour. The drying is preferably carried out in a vacuum oven.
[0040] In this invention, the preferred ratio of the zirconium salt to the functionalized silica is (0.25–40) mmol:(0.01–1.6) g, more preferably (0.5–30) mmol:(0.015–1.5) g, and specifically preferably 1 mmol:0.02 g. The mixing of the zirconium salt, the second hydrochloric acid, and the functionalized silica preferably includes the following steps: dissolving the zirconium salt in the second hydrochloric acid to obtain a zirconium salt solution; and mixing the zirconium salt solution with the functionalized silica.
[0041] After obtaining a cesium salt solution and a zirconium salt mixed solution, the present invention injects the cesium salt solution into the zirconium salt mixed solution to obtain the double perovskite / silica nanocomposite material. In this invention, the injection is preferably carried out under vigorous stirring conditions. The temperature of the zirconium salt mixed solution during injection is preferably room temperature. The injection is preferably carried out under open-air conditions. A white precipitate immediately forms after the cesium salt solution is injected into the zirconium salt mixed solution, and a crude liquid is obtained after the injection is completed. The present invention preferably performs solid-liquid separation of the crude liquid, and the obtained solid product is washed and dried to obtain the double perovskite / silica nanocomposite material. The solid-liquid separation is preferably centrifugation, the centrifugation speed is preferably 6000 rpm, and the time is preferably 2 min. The washing reagent is preferably methanol, and the washing is preferably performed 3 times. The drying temperature is preferably 50℃, and the drying time is preferably 1 h.
[0042] This invention provides a method for preparing a double perovskite / silica nanocomposite material as described in the above-mentioned technical solution. In the composite material provided by this invention, functionalized silica is attached to the surface of Cs₂ZrCl₆. The composite material provided by this invention maintains the high fluorescence quantum efficiency of Cs₂ZrCl₆ while significantly improving the storage stability of Cs₂ZrCl₆.
[0043] This invention provides the application of the double perovskite / silica nanocomposite material described above in the preparation of lighting or display materials. The double perovskite / silica nanocomposite material provided by this invention exhibits high fluorescence quantum efficiency and high storage stability, resulting in products with superior performance when used in the preparation of lighting or display materials.
[0044] To further illustrate the present invention, the technical solutions provided by the present invention will be described in detail below with reference to the embodiments, but they should not be construed as limiting the scope of protection of the present invention.
[0045] The raw materials used in the following examples include:
[0046] Cesium chloride (99.9% metals basis), zirconium chloride (≥99.9% metals basis), 3-aminopropyltriethoxysilane (APTES, >96.0%), 3-mercaptopropyltriethoxysilane (95%), 3-thiocyanopropyltriethoxysilane (99%), methanol (AR, 99.5%), ethanol (AR, water ≤0.3%), tetraethyl silicate (99.99% metals basis), ammonia (GR, 25–28%), purchased from Aladdin Reagent Network. Hydrochloric acid (36.0–38.0% in water), concentrated sulfuric acid (≥98%), purchased from Beijing Chemical Reagent Co., Ltd., China.
[0047] Comparative Example 1
[0048] The preparation method of the Cs2ZrCl6 product provided in this comparative example includes the following steps:
[0049] 2 mmol CsCl and 1 mmol ZrCl4 were dissolved in 1.25 mL and 2.7 mL of hydrochloric acid, respectively, to obtain 1.25 mL of CsCl solution and 2.7 mL of ZrCl4 solution. Under vigorous stirring, 1.25 mL of CsCl solution was rapidly added to 2.7 mL of ZrCl4 solution, and a white precipitate immediately formed at room temperature and in open-air conditions. The product was extracted from the crude solution, centrifuged (6000 rpm, 2 min), washed three times with methanol solution, and dried at 50 °C for 2 h to obtain Cs₂ZrCl₆.
[0050] Example 1
[0051] The preparation method of the Cs2ZrCl6@SiO2-NH2 product provided in this embodiment includes the following steps:
[0052] First, a mixture containing 250 mL of ethanol, 20 mL of water, and 8 mL of ammonia was added to a flask. After stirring for 1 hour, tetraethyl orthosilicate (15 mL) was slowly added, and the mixture was stirred in a water bath (40 °C) for 3 hours. The resulting SiO2 was obtained by centrifugation, then washed four times with ethanol and deionized water, and dried in a vacuum oven at 60 °C for 4 hours.
[0053] A liquid H2O2 solution (20 mL) was slowly added to a concentrated H2SO4 solution (20 mL), and the mixture was gently stirred with a glass rod at room temperature to obtain a mixed solution. 0.2 g of SiO2 was dissolved in 40 mL of the mixed solution (H2SO4:H2O2 volume ratio 1:1), and stirred for 10 min. The solution was then centrifuged to obtain hydroxyl SiO2 nanospheres, i.e., SiO2-OH nanospheres. These nanospheres were washed three times with ultrapure water and dried in a vacuum oven at 80 °C for 1 h.
[0054] SiO2-OH spheres (0.3g), ethanol (10mL), and APTES (1mL) were stirred for 20h, centrifuged, washed three times with ethanol solution, and dried at 80℃ for 1h to prepare aminated SiO2 spheres, namely SiO2-NH2.
[0055] 2 mmol CsCl and 1 mmol ZrCl4 were dissolved in 1.25 mL and 2.7 mL of hydrochloric acid, respectively, to obtain 1.25 mL of CsCl solution and 2.7 mL of ZrCl4 solution. 0.02 g SiO2-NH2 was dissolved in 2.7 mL of ZrCl4 solution and stirred for 1 h to obtain 2.7 mL of ZrCl4 mixed solution.
[0056] Under vigorous stirring, 1.25 mL of CsCl solution was rapidly injected into 2.7 mL of a ZrCl4 mixed solution, and a white precipitate was immediately formed at room temperature and in open air. The product was extracted from the crude solution, centrifuged (6000 rpm, 2 min), washed three times with methanol solution, and dried at 50 °C for 2 h to obtain Cs2ZrCl6@SiO2-NH2.
[0057] Example 2
[0058] The preparation method of the Cs2ZrCl6@SiO2-SH product provided in this embodiment includes the following steps:
[0059] First, a mixture containing 250 mL of ethanol, 20 mL of water, and 8 mL of ammonia was added to a flask. After stirring for 1 hour, tetraethyl orthosilicate (15 mL) was slowly added, and the mixture was stirred in a water bath (40 °C) for 3 hours. The resulting SiO2 was obtained by centrifugation, then washed four times with ethanol and deionized water, and dried in a vacuum oven at 60 °C for 4 hours.
[0060] Liquid H2O2 (20 mL) was slowly added to concentrated H2SO4 (20 mL), and the mixture was gently stirred with a glass rod at room temperature to obtain a mixed solution. 0.2 g of SiO2 was dissolved in 40 mL of the mixed solution (H2SO4:H2O2 volume ratio 1:1) and stirred for 10 min. After centrifugation, hydroxyl SiO2 nanospheres, namely SiO2-OH spheres, were obtained. The nanospheres were washed three times with ultrapure water and dried in a vacuum oven at 80 °C for 1 h.
[0061] SiO2-OH spheres (0.3 g), ethanol (10 mL), and 3-mercaptopropyltriethoxysilane (1 mL) were stirred for 20 h, centrifuged, washed three times with ethanol solution, and dried at 80 °C for 1 h to prepare thiolized SiO2 spheres, namely SiO2-SH.
[0062] 2 mmol CsCl and 1 mmol ZrCl4 were dissolved in 1.25 mL and 2.7 mL of hydrochloric acid, respectively, to obtain 1.25 mL of CsCl solution and 2.7 mL of ZrCl4 solution. 0.02 g SiO2-SH was dissolved in 2.7 mL of ZrCl4 solution and stirred for 1 h to obtain 2.7 mL of ZrCl4 mixed solution.
[0063] Under vigorous stirring, 1.25 mL of CsCl solution was rapidly injected into 2.7 mL of a ZrCl4 mixed solution, and a white precipitate was immediately formed at room temperature and in open air. The product was extracted from the crude solution, centrifuged (6000 rpm, 2 min), washed three times with methanol solution, and dried at 50 °C for 2 h to obtain Cs2ZrCl6@SiO2-SH.
[0064] Example 3
[0065] The preparation method of the Cs2ZrCl6@SiO2-SCN product provided in this embodiment includes the following steps:
[0066] First, a mixture containing 250 mL of ethanol, 20 mL of water, and 8 mL of ammonia was added to a flask. After stirring for 1 hour, tetraethyl orthosilicate (15 mL) was slowly added, and the mixture was stirred in a water bath (40 °C) for 3 hours. The resulting SiO2 was obtained by centrifugation, then washed four times with ethanol and deionized water, and dried in a vacuum oven at 60 °C for 4 hours.
[0067] Liquid H2O2 (20 mL) was slowly added to concentrated H2SO4 (20 mL), and the mixture was gently stirred with a glass rod at room temperature to obtain a mixed solution. 0.2 g of SiO2 was dissolved in 40 mL of the mixed solution (H2SO4:H2O2 volume ratio 1:1) and stirred for 10 min. After centrifugation, hydroxyl SiO2 nanospheres, namely SiO2-OH spheres, were obtained. The nanospheres were washed three times with ultrapure water and dried in a vacuum oven at 80 °C for 1 h.
[0068] SiO2-OH spheres (0.3 g), ethanol (10 mL), and 3-thiocyanopropyltriethoxysilane (1 mL) were stirred for 20 h, centrifuged, washed three times with ethanol solution, and dried at 80 °C for 1 h to prepare thiocyanated SiO2 spheres, namely SiO2-SCN.
[0069] 2 mmol CsCl and 1 mmol ZrCl4 were dissolved in 1.25 mL and 2.7 mL hydrochloric acid, respectively, to obtain 1.25 mL CsCl solution and 2.7 mL ZrCl4 solution, respectively. 0.02 g SiO2-SCN was dissolved in 2.7 mL ZrCl4 solution and stirred for 1 h to obtain 2.7 mL ZrCl4 mixed solution.
[0070] Under vigorous stirring, 1.25 mL of CsCl solution was rapidly injected into 2.7 mL of a ZrCl4 mixed solution, and a white precipitate was immediately formed at room temperature and in open air. The product was extracted from the crude solution, centrifuged (6000 rpm, 2 min), washed three times with methanol solution, and dried at 50 °C for 2 h to obtain Cs2ZrCl6@SiO2-SCN.
[0071] Test case
[0072] Figure 1 The images show the XRD patterns of the products prepared in Examples 1-3 and Comparative Example 1. Figure 1 It can be seen that the XRD patterns of Cs2ZrCl6@SiO2-NH2 prepared in Example 1, Cs2ZrCl6@SiO2-SH prepared in Example 2, and Cs2ZrCl6@SiO-SCN prepared in Example 3 correspond well with the diffraction peaks of the Cs2ZrCl6 standard card.
[0073] Figure 2 SEM images of the products prepared in Examples 1-3 and Comparative Example 1, by... Figure 2 It can be seen that the morphology of Cs2ZrCl6 prepared in Comparative Example 1 is octahedral particles. Scanning electron microscopy of Cs2ZrCl6@SiO2-NH2 prepared in Example 1, Cs2ZrCl6@SiO2-SH prepared in Example 2, and Cs2ZrCl6@SiO2-SCN prepared in Example 3 shows that functionalized SiO2 is embedded on the surface of Cs2ZrCl6.
[0074] The morphology of the products prepared in Examples 1-3 changed significantly compared to the products in the comparative examples.
[0075] Figure 3 The absolute quantum efficiency (PLQY) of the products prepared in Examples 1-3 and Comparative Example 1 is given by... Figure 3 It can be seen that the absolute quantum efficiency (PLQY) of Cs2ZrCl6@SiO2-NH2 prepared in Example 1 is 78.08%, the absolute quantum efficiency (PLQY) of Cs2ZrCl6@SiO2-SH prepared in Example 2 is 87.29%, and the absolute quantum efficiency (PLQY) of Cs2ZrCl6@SiO2-SCN prepared in Example 3 is 89.48%. The absolute quantum efficiency (PLQY) of Cs2ZrCl6 is 70.26%.
[0076] Figure 4 The storage stability (112 days of storage) of the products prepared in Examples 1-3 and Comparative Example 1 was determined by... Figure 4 It can be seen that the products prepared in Examples 1 to 3 of the present invention have good storage stability.
[0077] As shown in the above embodiments, the present invention provides a method for preparing a double perovskite / silica nanocomposite material, comprising the following steps: mixing cesium salt and hydrochloric acid to obtain a cesium salt solution; mixing zirconium salt, hydrochloric acid, and functionalized silica to obtain a zirconium salt mixed solution, wherein the functionalized silica includes one or more of SiO2-NH2, SiO2-SH, and SiO2-SCN; and injecting the cesium salt solution into the zirconium salt mixed solution to obtain the double perovskite / silica nanocomposite material. The present invention uses functionalized silica as a nucleation site for Cs2ZrCl6, successfully synthesizing double perovskite / silica nanocomposite materials (Cs2ZrCl6@SiO2-NH2, Cs2ZrCl6@SiO2-SH, and Cs2ZrCl6@SiO2-SCN in the embodiments), which significantly improves the storage stability of Cs2ZrCl6 while maintaining its high fluorescence quantum efficiency. Meanwhile, the preparation method provided by this invention is simple, and significantly improves the stability of double perovskite without changing the original preparation process and equipment of Cs2ZrCl6 double perovskite, making it suitable for industrial production.
[0078] Although the above embodiments have provided a detailed description of the present invention, they are only some embodiments of the present invention, and not all embodiments. Other embodiments can be obtained based on these embodiments without creative effort, and these embodiments all fall within the protection scope of the present invention.
Claims
1. A method for preparing a double perovskite / silica nanocomposite material, characterized in that, Includes the following steps: Cesium salt and hydrochloric acid are mixed to obtain a cesium salt solution; Zirconium salt, hydrochloric acid, and functionalized silica are mixed to obtain a zirconium salt mixed solution, wherein the functionalized silica is one or more of mercapto-modified SiO2 spheres SiO2-SH and thiocyanate-modified SiO2 spheres SiO2-SCN; The cesium salt solution is injected into the zirconium salt mixed solution to obtain the double perovskite / silica nanocomposite material.
2. The preparation method according to claim 1, characterized in that, The method for preparing the functionalized silica includes the following steps: Hydrogen peroxide, concentrated sulfuric acid and silicon dioxide are mixed and subjected to a hydroxylation reaction to obtain SiO2-OH; The SiO2-OH, alcohol solvent, and functionalizing reagent are mixed and modified to obtain the functionalized silica. The functionalizing reagent includes one or more of silane coupling agents containing mercapto groups and silane coupling agents containing thiocyano groups.
3. The preparation method according to claim 2, characterized in that, The functionalizing agent includes one or more of 3-mercaptopropyltriethoxysilane and 3-thiocyanopropyltriethoxysilane.
4. The preparation method according to claim 1, characterized in that, The molar ratio of the cesium salt to the zirconium salt is (0.5~80):(0.25~40).
5. The preparation method according to claim 1 or 4, characterized in that, The ratio of zirconium salt to functionalized silica is (0.25~40) mmol: (0.01~1.6) g.
6. The preparation method according to claim 2, characterized in that, The concentrated sulfuric acid has a mass percentage content of ≥98%, and the volume ratio of hydrogen peroxide to concentrated sulfuric acid is 1:1; the amount ratio of hydrogen peroxide to silicon dioxide is (10~50) mL: (0.1~0.5) g.
7. The preparation method according to claim 2 or 6, characterized in that, The alcohol solvent is ethanol; the ratio of SiO2-OH, alcohol solvent and functionalizing reagent is (0.1~0.4) g : (5~20) mL : (0.5~2) mL.
8. The preparation method according to claim 2, characterized in that, The method for preparing the silicon dioxide includes the following steps: Ethanol, water, ammonia, and tetraethyl orthosilicate are mixed and hydrolyzed to obtain silicon dioxide; the mass percentage of ammonia is 25-28%, and the volume ratio of ethanol, water, ammonia, and tetraethyl orthosilicate is (250-500):(20-40):(8-16):(15-30); the hydrolysis reaction is carried out at a temperature of 35-50°C for 2.5-4 hours.
9. The preparation method according to any one of claims 1 to 8 yields a double perovskite / silica nanocomposite material.
10. The application of the double perovskite / silica nanocomposite material according to claim 9 in the preparation of lighting materials or display materials.